Professional and Personality Competency in Prophetic Counseling: A Phenomenological Study of School Counselors - Casmini, Casmini; Hasanah, Enung (International Journal of Islamic Educational Psychology, 2024)
Balancing transcendental and worldly values through prophetic counseling is crucial for preventing mental disorders and addressing global socio-cultural challenges. Prophetic counseling focuses on spiritual and afterlife concerns, unlike traditional counseling, which centers on worldly matters. The purpose of this study is to explore prophetic values and internalization experienced by counselors at school. This study is a qualitative research that used Descriptive Phenomenological Psychology. Data were obtained by interviewing three guidance and counseling teachers from Islamic schools. Data analysis was carried out by arranging the description and categorization based on the founding of the theme that intrigued and internalized the values of prophetic counseling at school. The result showed that prophetic in school counseling by the counselors was drawn into two aspects: professional competency, which is applied in approach, strategy, technique, or method of guidance and counseling, and personality competency, which tends to reflect their personal character. Internalization of prophetic values gradually occurred through the relationship of counselor-counselee in the guidance and counseling, which has been turned into a method for adding new knowledge and improving counselor attitude and behavior